Expression of the TIGIT axis and the CD39/CD73 purinergic pathway in bone metastasis-derived immune cells - Elias Brauneck; Leon-Gordian Leonhardt; Anne Marie Assemissen; Yagana Wahid; Moritz Kruppa; Niklas Kruppa; Julius Krüger; Stephan Menzel; Friedrich Koch-Nolte; Julian Kylies; Katja Weisel; Carsten Bokemeyer; et al. (Cancer Immunology, Immunotherapy)
Abstract Background Bone metastases (BM) represent one of the most common sites of metastasis. The study aimed to compare the composition of immune cell infiltration from aspirates of different BM prior to systemic therapy. Method Phenotypic and functional analyses were conducted via multiparametric flow cytometry (MFC) on BM-derived aspirates obtained from patients with breast cancer (BC, n = 6), patients with prostate cancer (PC, n = 5), patients with non-small-cell lung cancer (NSCLC) (n = 7), patients with myeloma (MM, n = 10) and bone aspirates from age-matched non-malignant controls (NMC, n = 10). Results Across all tumors aspirates the fraction of CD8+ T cells was reduced. In contrast, infiltration by immunosuppressive CD56+CD16−NK and CD163+CD86+ M2-like macrophages was increased in BM compared to NMC aspirates. BM-derived CD8+ T cells aberrantly co-expressed TIGIT with PVRIG or CD39. Similarly, BM-derived cytotoxic NK cells co-expressed TIGIT and PVRIG. In addition, BM-derived M2-like macrophages exhibited an increased subset of cells co-expressing either TIGIT and PVRL4 or CD112 and CD155. Using a myeloma model, functional in vitro studies showed that blockade of TIGIT and CD39 leads to increased PBMC-mediated lysis of myeloma cells. Conclusion The study shows that an altered immune cell composition is present in BM across the different tumor entities. Additionally, molecules of the TIGIT checkpoint as well as of the purinergic pathway are aberrantly expressed by BM-infiltrating CD8+ T cells, NK cells and macrophages and also functionally relevant for tumor cell lysis.